2007
DOI: 10.1074/jbc.m610347200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures and Site-directed Mutagenesis of a Mycothiol-dependent Enzyme Reveal a Novel Folding and Molecular Basis for Mycothiol-mediated Maleylpyruvate Isomerization

Abstract: Mycothiol (MSH) is the major low molecular mass thiols in many Gram-positive bacteria such as Mycobacterium tuberculosis and Corynebacterium glutamicum. The physiological roles of MSH are believed to be equivalent to those of GSH in Gramnegative bacteria, but current knowledge of MSH is limited to detoxification of alkalating chemicals and protection from host cell defense/killing systems. Recently, an MSH-dependent maleylpyruvate isomerase (MDMPI) was discovered from C. glutamicum, and this isomerase represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Since its discovery in 1993 (6,48), MSH has been shown to be involved in many processes. Next to its role as a storage form of cysteine in Mycobacterium smegmatis (49) and its detoxification role for alkylating agents (50), there are only two enzymes described that depend on MSH for functioning: formaldehyde dehydrogenase MscR (51), later identified as nitrosomycothiol reductase, with a role in the protection against oxidative stress (52), and maleylpyruvate isomerase (22,53). We present the first enzymes, arsenate reductase 1 and 2, from C. glutamicum, which depend for their function on mycothiol as well as on mycoredoxin with a clear link to the mycothione reductase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery in 1993 (6,48), MSH has been shown to be involved in many processes. Next to its role as a storage form of cysteine in Mycobacterium smegmatis (49) and its detoxification role for alkylating agents (50), there are only two enzymes described that depend on MSH for functioning: formaldehyde dehydrogenase MscR (51), later identified as nitrosomycothiol reductase, with a role in the protection against oxidative stress (52), and maleylpyruvate isomerase (22,53). We present the first enzymes, arsenate reductase 1 and 2, from C. glutamicum, which depend for their function on mycothiol as well as on mycoredoxin with a clear link to the mycothione reductase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the dominant activity is that of an MSH-dependent maleylpyruvate isomerase but that a lower-level, thiol-independent activity may also be present. The MSH-dependent maleylpyruvate isomerase from C. glutamicum has been crystallized and, unlike the human GSH-dependent enzyme, was found to be a zinc metalloprotein with a novel fold (153). The MSH-dependent maleylpyruvate isomerase also lacked the dehalogenation activity found for the human enzyme.…”
Section: Maleylpyruvate Isomerasementioning
confidence: 99%
“…The C-terminal domain is necessary for the enzyme activity and structural stability. Furthermore, site-directed mutagenesis revealed that the Arg 222 residue at the C-terminal domain was necessary for MDMPI activity (Wang et al 2007). The discovery of a mycothiol-dependent maleylpyruvate isomerase (MDMPI) in C. glutamicum introduced a new category of maleylpyruvate isomerase, and constitutes significant progress on the way to understanding both the gentisate pathway of aromatic assimilation and the MSH physiology (Rawat and Av-Gay 2007).…”
Section: Glutamicum Assimilates Diverse Aromatic Compoundsmentioning
confidence: 99%